COMPARISON OF HIGHEST AND LOWEST ENVIRONMENTAL DISCLOSURE REPORTS BEFORE ANDDURING THE COVID-19 PANDEMIC (IN THE ANNUAL REPORT OF COMPANIES LISTED ON THE IDX) - Kaharti, Eni (Politeknik Sawunggalih Aji, 2023)
This study aims to compare environmental disclosures made by publicly traded companies in Indonesia before and during the covid 19 pandemic. The sample used was manufacturing companies listed on the Indonesia Stock Exchange in 2019 and 2020. The test equipment used was the Paired test sample. This research has never been carried out by previous researchers, in this study the focus is on manufacturing companies because this type of company contributes quite a lot to environmental waste. The benefit is to find out the distribution of differences in the conditions of environmental disclosure reports in Indonesia during the covid 19 pandemic. attention to the environment. The results of this study indicate that there are material differences in environmental disclosures before and during the Cofid period. However, the companies that gave the highest environmental disclosures at the time and before the pandemic were carried out by the same companies. The highest items in environmental disclosure are, greenhouse gas emissions, water treatment and water disposal Keywords: comparison, environmental disclosure, covid 19 pandemic